Carbohydrate use and reduction in number of balance beam falls: implications for mental and physical fatigue - Pereira Batatinha, H. A.; da Costa, C. E.; de Franca, E.; Dias, I. R.; Xavier Ladeira, A. P.; Rodrigues, B.; Santos de Lira, F.; Cavalcante Correia, S.; Chagas Caperuto, E. (Journal of the International Society of Sports Nutrition, 2013)
Artistic Gymnastics is a sport where athletes are frequently fatigued. One element that might influence this aspect is carbohydrate, an important energy substrate for the muscles and the CNS. Our goal was to investigate the influence of fatigue over artistic gymnastics athlete`s performance and the effects of a carbohydrate supplementation on their performance. Methods: We evaluated 15 athletes divided in 2 groups (control and fatigue) from 12 to 14 years old in two different experimental days. On the first day (water day), they did 5 sets of exercises on the balance beam (experimental protocol) ingesting only water, CG (control group) warmed up before the experimental protocol and FG (fatigue group) did a fatigue circuit, warm up exercises and then the experimental protocol. On the second day (carbohydrate day), we used the same protocol but CG ingested a sugar free flavored juice and FG ingested a 20% concentration maltodextrin solution before the protocol on the balance beam. Results: We observed a greater number of falls from the balance beam from the FG on the first day (5.40 ± 1.14 FG vs 3.33 ± 1.37 CG; p = 0.024) and a decrease in the number of falls on the second day (2.29 ± 1.25 FG water day vs 5.40 ± 1.14 FG carbohydrate day; p = 0.0013). Carbohydrate solution was able to supply muscle demands and improve the athlete`s focus showed by the reduced number of falls.